The Role of Quantitative Techniques and Devices in Military Geography: Political Geography Study - Yadgar Abdullah Ali (QALAAI ZANIST JOURNAL, 2022)
This study aims at exploring the different stages through which the Military Geography has gone, starting from the early stages of Descriptive Geography to the Quantitative Revolution, Statistics; the level at which the revolution of information technology and geographical systems emerged; the use of artificial intelligence-oriented devices to analyze geographical locations and arriving at plausible decisions in different spheres. More particularly, in the field of military geography in which there exist a strong relation between the military activities and geographical locations and environments which are highly inseparable, because the earth appears to be a show for military operations from its both natural and humanity perspectives. The significance of this study lies in the fact that a rapid development is perceived in the field of using Geographic Information System (GIS), finding and determining locations, analyzing geographical phenomena and assessing them within military geography. What is considered as a problem in this study is the fact that the developing countries have been relatively incapable of taking advantage of this system (GIS) in the realm of military geography. The significant reason for this is the high cost it takes and it needs high skills and proficiency which makes it hard to obtain it. In addition, the developing countries are not being provided with assistance to utilize the system. This study depends on extraction method and styled system with force analysis to achieve the objectives of the study.